2019
DOI: 10.1002/aur.2220
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between parent and child ratings of anxiety in children with autism spectrum disorder

Abstract: Co-occurring anxiety is common in children with autism spectrum disorder (ASD). However, inconsistencies across parent and child reports of anxiety may complicate the assessment of anxiety in this population. The present study examined parent and child anxiety ratings in children with ASD with and without anxiety disorders and tested the association between parent-child anxiety rating discrepancy and ASD symptom severity. Participants included children aged 8-16 years in three diagnostic groups: ASD with co-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 42 publications
(86 reference statements)
2
20
0
Order By: Relevance
“…The mean ratings of anxiety and impairment from both parents are in line with the diagnostic interview and this is worth noticing, as the scores from the fathers can be considered more independent of the interview. All informants have scores in the same direction, although not all reach statistical significance, and in line with previous literature ( 55 ), the children report lower levels of anxiety compared to the parents. These patterns of parent and child ratings could result from children with ASD and comorbid anxiety having difficulty in reporting their anxiety while the parents are more aware of them.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mean ratings of anxiety and impairment from both parents are in line with the diagnostic interview and this is worth noticing, as the scores from the fathers can be considered more independent of the interview. All informants have scores in the same direction, although not all reach statistical significance, and in line with previous literature ( 55 ), the children report lower levels of anxiety compared to the parents. These patterns of parent and child ratings could result from children with ASD and comorbid anxiety having difficulty in reporting their anxiety while the parents are more aware of them.…”
Section: Discussionsupporting
confidence: 90%
“…Partial remission is a tentative definition of the increased occasional use of language sometimes found in children treated for selective mutism also when using defocused communication and graded exposure in an especially designed home-and school based intervention for this condition ( 64 ). Furthermore, a majority had comorbid ADHD, and three of the ten children had a depressive episode, in line with a study showing that children with ASD and comorbid anxiety have more ADHD and other comorbid disorders compared to children with ASD and no anxiety disorder ( 55 ). The comorbidity did not seem to affect outcome in our study, as also shown in a recent study reporting no clear differential impact of co-occurring psychiatric disorders on response to anxiety treatment ( 65 ).…”
Section: Discussionsupporting
confidence: 85%
“…The finding may be accounted for by several reasons. First, interrater disagreement has been welldocumented in youth with (Kalvin et al, 2020) and without (Dirks et al, 2014) ASD and may explain, in part, why differences did not emerge in Child stress. Parentchild agreement has been associated with better youth outcomes (e.g., anxiety; Burrows et al, 2018) and highlights the importance of understanding multiple perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for these discrepancies could be the instruments themselves: poor psychometrics may lead to discrepant reports. However, the instruments used in these studies have been shown to have strong internal reliability (Spence, 1998;Klassen et al, 2006;Kalvin et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…But, there are also constructs where the parent and child reports of the child's experiences do not match. For example, Kalvin et al (2019) and Lagattuta et al (2012) did not find a significant correlation between parent and child reports of the child's level of anxiety (r = 0.02 and rs < 0.10, respectively; Lagattuta et al (2012) compare parent and child reports over multiple subscales). Likewise, parents of children diagnosed with attention deficit/hyperactivity disorder tended to underestimate (relative to the child report) their child's self-esteem and mental health and over-estimate their physical function (Klassen et al, 2006).…”
Section: Introductionmentioning
confidence: 98%